Missing Cells: Pathophysiology, Diagnosis, and Management of (Pan)Cytopenia in Childhood - Erlacher, Miriam; Strahm, Brigitte (Frontiers in Pediatrics, 2015)
Peripheral blood cytopenia in children can be due to a variety of acquired or inherited diseases. Genetic disorders affecting a single hematopoietic lineage are frequently characterized by typical bone marrow findings such as lack of progenitors or maturation arrest in congenital neutropenia or a lack of megakaryocytes in congenital amegakaryocytic thrombocytopenia whereas antibody mediated diseases such as autoimmune neutropenia are associated with a rather unremarkable bone marrow morphology. In contrast, pancytopenia is frequently associated with a hypocellular bone marrow and the differential diagnosis includes acquired aplastic anemia, myelodysplastic syndrome, inherited bone marrow failure syndromes such as Fanconi anemia and dyskeratosis congenita and a variety of immunological disorders including hemophagocytic lymphohistiocytosis. Thorough bone marrow analysis is of special importance for the diagnostic work-up of most patients. Cellularity, cellular composition and dysplastic signs are the cornerstones of the differential diagnosis. Pancytopenia in the presence of a normo- or hypercellular marrow with dysplastic changes may indicate myelodysplastic syndrome. More challenging for the hematologist is the evaluation of the hypocellular bone marrow. Although aplastic anemia and hypocellular refractory cytopenia of childhood (RCC) can reliably be differentiated on a morphological level the overlapping pathophysiology remains a significant challenge for the choice of the therapeutic strategy. Furthermore, inherited bone marrow failure syndromes are usually associated with the morphological picture of RCC and the recognition of these entities is essential as they often present a multisystem disease requiring different diagnostic and therapeutic approaches. This paper gives an overview over the different disease entities presenting with (pan)cytopenia, their pathophysiology, characteristic bone marrow findings and therapeutic approaches.